REMINDER EFFECT AND ANCHORING-ADJUSTMENT IN EARNINGS ANNOUNCEMENT: IMPLEMENTATION OF PRIORPERIOD BENCHMARK DISCLOSURE STRATEGY - Wahyuni, Sri; HM, Jogiyanto (Journal of Indonesian Economy and Business, 2012)
The purpose of this study is to provide empirical support regarding the reminder effectsÂ and anchoring-adjustment in earnings announcements. This study is important to explainthe cognitive mechanism in processing the information that the consequences can affectÂ the judgments of investors in evaluating company performance. The research of behavioralaccounting often focuses on the consideration in the framework of investment decision makingÂ mechanism based on a systematic and accurate. Prior researches have describedÂ strategic disclosure of prior-period benchmark in earnings announcement that focuses onÂ the transitory gain or loss, which, in turn, influences investorâs judgments (Schrand &Â Walther 2000; Krische 2005). Using strategic reference-point theory from psychology andÂ Hogarth & Einhornâs (1992) belief-adjustment theory, this paper extends such research byÂ investigating how investors behave differently to reminder effect and anchoringadjustment.Â The experimental results suggest that reminder effects and anchoring ofÂ information can influences investorâs judgments in evaluating of company performance.Keywords: reminder effect, anchoring-adjustment, cognitive mechanism, strategicÂ reference-point theory, belief- adjustment theory